Cryopreservation of human granulocytes in liquid nitrogen. Issue 8 (August 1977) - Graham-Pole, J; Davie, M; Willoughby, M L
Abstract : Human granulocytes (PMNL) were successfully cryopreserved for up to 14 months. The PMNL (1-2 X 10(7)/ml) were stored in 2-ml ampoules in the gas phase of liquid nitrogen at a temperature between -160 degrees C and -196 degrees C using dimethylsulphoxide (DMSO 10%) as cryoprotectant. Morphology and phagocytic and bactericidal capacity were best preserved by adding fetal calf serum to the freezing mixture, by using an interrupted cooling process, by washing the thawed PMNL in fresh freeze-dried plasma, and centrifuging at 600 g for no more than two minutes. Careful post-thaw handling of the cells was an important factor in preserving function. These preliminary studies indicate that useful numbers of PMNL can be recovered in a functional state after storage for long periods in liquid nitrogen.